Pengaruh Teknologi Digital, Strategi Pemasaran Online, dan Inovasi Produk Terhadap Keunggulan Kompetitif UMKM di Kota Palu - Mutmainah Mutmainah; Armawati Armawati; Tovan Tovan (Jurnal Ilmu Manajemen METHONOMIX, 2024)
This research aims to determine the simultaneous and partial influence of digital technology, online marketing strategies, and product innovation on the competitive advantage of MSMEs in Palu City, Central Sulawesi Province. This research uses a quantitative approach with survey methods. The relationship between variables was examined and analyzed using SPSS software.Questionnaires were distributed to 50 MSME respondents and explained. The results of this research show that (1) digital technology, online marketing strategies, and product innovation simultaneously have a significant effect on competitive advantage. (2) digital technology has a significant effect on competitive advantage. (3) online marketing strategy has a significant effect on competitive advantage. (4) product innovation has a significant effect on the competitive advantage of MSMEs in Palu City